Physico-Chemical Properties of Calcium-Fortified Analog Rice from Composite Flour (Cassava, Corn, and Snakehead Fish) for Osteoporosis Prevention - Sumardiono, Siswo; Pudjihastuti, Isti; Supriyo, Edy; Amalia, Rizka (Journal of Vocational Studies on Applied Research, 2020)
In this study, composite flour made from cassava and corn flour were processed for producing analog rice. To meet the calcium needs for the elderly andto optimize the potential of cassava, corn, and snakehead fish, the analog rice will be fortified with calcium from cork fish. The aim of this work are to study the effect of composite flour composition  and the extruxtion temperature on the physico-chemical properties of calcium-fortified analog rice. The parameter process studied were mocaf flour:snakehead fish flour (MF/SFF) mass ratio (100:0; 97:3; 94 6; 91:9; and 88:12) and extrusion temperature ranging from 50oC, 70oC, and  90oC. The physico-chemical properties including bulk density, cooking time, proximate, calcium levels and its organoleptic were analyzed. The results showed that at 91:9 MF/SFF mass ratio  and  the extrusion temperature at 70oC obtain the best effect on the nutrient content of analog rice which contain 14.34% of water, 0.85% of ash, 71.829% of carbohydrate, 11.236% of  protein, 1.12% of fat , 1,113 ppm of calcium, and 2.427% of dietary fibre.